2020
DOI: 10.1371/journal.pone.0228945
|View full text |Cite
|
Sign up to set email alerts
|

1,25-hydroxyvitamin D3 decreases endoplasmic reticulum stress-induced inflammatory response in mammary epithelial cells

Abstract: Recent studies indicated that intramammary administration of active vitamin D 3 hormone (1,25D 3 ) inhibits the inflammatory process associated with mastitis. We hypothesized that attenuation of endoplasmic reticulum (ER) stress by 1,25D 3 in mammary epithelial cells (MECs) is an important cellular mechanism contributing to this beneficial effect of intramammary treatment with 1,25D 3 . To test this hypothesis, the effect of 1,25D 3 was studied on induction of ER stress in a transformed human MEC line, MCF-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…Increasing studies have reported VD-mediated inhibition of ER stress play key roles in various diseases. VD3 treatment decreased ER stress-induced inflammatory response in mammary epithelial cells (Wen et al, 2020). Moreover, VD treatment promoted proliferation, inhibited apoptosis, reduced the levels of endogenous markers of ER stress in human umbilical vein endothelial cells, and improved the impaired wound healing in diabetic mice by suppressing ER stress (Yuan et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Increasing studies have reported VD-mediated inhibition of ER stress play key roles in various diseases. VD3 treatment decreased ER stress-induced inflammatory response in mammary epithelial cells (Wen et al, 2020). Moreover, VD treatment promoted proliferation, inhibited apoptosis, reduced the levels of endogenous markers of ER stress in human umbilical vein endothelial cells, and improved the impaired wound healing in diabetic mice by suppressing ER stress (Yuan et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Although fibroblasts are the major contributors to airway remodeling in asthma and COPD, other cell types within the lung, including smooth muscle cells are also involved. On the other hand, vitamin D3 through its active metabolite 1,25D3, is known to possess anti-inflammatory and anti-fibrotic mechanisms (26)(27)(28), and have shown to improve immune responses (29,30). Therefore, we investigated the role of 1,25D3 in polyI:C-induced pro-inflammatory and pro-fibrotic responses in primary BSMCs isolated from subjects with asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…After reaching confluence, cells were treated with either 10 µM RSV, 0.1 µg/mL TM or 10 µM RSV combined with 0.1 µg/mL TM or 0.1% DMSO as vehicle control in 6H medium for 6 or 48 h. Following treatment, total RNA was extracted from cells using Trizol reagent (Invitrogen, Karlsruhe, Germany) according to the manufacturer’s protocol. The synthesis of cDNA and qPCR analysis were performed as described recently in detail [ 52 , 53 , 54 ]. Characteristics of gene-specific primers synthesized by Eurofins MWG Operon (Ebersberg, Germany) are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%